2022
DOI: 10.1242/dev.200292
|View full text |Cite
|
Sign up to set email alerts
|

Different temporal requirements for tartan and wingless in the formation of contractile interfaces at compartmental boundaries

Abstract: Compartmental boundaries physically separate developing tissues into distinct regions, which is fundamental for the organization of the body plan in both insects and vertebrates. In many examples, this physical segregation is caused by a regulated increase in contractility of the actomyosin cortex at boundary cell-cell interfaces, a property important in developmental morphogenesis beyond compartmental boundary formation. We performed an unbiased screening approach to identify cell surface receptors required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…While there is some de-repression of both sim and ind in the non-invaginated mesoderm and in the mesectoderm in twist mutants, the expression of all 3 genes is similar in the ectoderm ( S2 Fig ). We also checked the expression patterns of the Leucine-rich repeat (LRR) cell surface receptors Tolls 2, 6, 8, and Tartan, which are required for the polarised distribution of Myosin II during GBE downstream of the AP patterning genes [ 22 , 44 47 ]. We confirmed that these genes are expressed with the same patterns in twist mutants as in wild type ( S2 Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While there is some de-repression of both sim and ind in the non-invaginated mesoderm and in the mesectoderm in twist mutants, the expression of all 3 genes is similar in the ectoderm ( S2 Fig ). We also checked the expression patterns of the Leucine-rich repeat (LRR) cell surface receptors Tolls 2, 6, 8, and Tartan, which are required for the polarised distribution of Myosin II during GBE downstream of the AP patterning genes [ 22 , 44 47 ]. We confirmed that these genes are expressed with the same patterns in twist mutants as in wild type ( S2 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…To compare averaged metrics between wild type and twist mutants, we synchronised the movies in time, using the start of tissue extension along the AP axis (measured as AP tissue strain rate) in each movie as time zero as before ( Methods ) ( S3A and S3B Fig ) [ 3 , 4 , 26 , 47 ]. To check that timelines of wild-type and twist mutant movies were comparable once synchronised, we checked the timings of 2 developmental events: (i) when Myosin II becomes detectable apically in the ectoderm; and (ii) when the first cell divisions occur ( Methods ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In tartan mutant embryos, polarity is strongly decreased at cell-cell contacts between column 4 (Tartan+) and column 5 (Tartan−) as well as between column 8 (Tartan−) and column 1 (Tartan+), whereas polarity is not significantly affected at cell-cell contacts inside the Tartan stripe [ 39 ]. There is at least one stripe border at every position of the LRR module ( Figure 2B ), and evidence suggests that these four receptors account for the vast majority of planar polarity in the Drosophila neuroectoderm [ 39 , 42 , 43 ]. Of course, parasegments are not perfectly rectangular grids of hexagons, and this digital model of receptor expression is a necessary simplification of reality.…”
Section: Striped Leucine-rich Repeat Receptors Link Embryonic Pattern...mentioning
confidence: 99%